The Effect of Monomers Molar Ratio on Degree of Absorptivity of Poly (AAc - co -AAm) as a Super Absorbent Polymer in Different Aqueous Solutions - Mahdi M. Almaky, Saleh N. Abdulla,Maryam J. Ehmaida, Najlaa A. Rafaa, Fatma A. Abdulsalam, Rajab A. Mega, Abdurrahman A. Khalifa, (Journal of Pure & Applied Sciences, 2020)
In this research the Super Absorbent Polymers (SAPs) were prepared by free-radical crosslinking copolymerization with different molar ratios of acrylamide (AAm) with partially neutralized acrylic acid (AAc) in aqueous solutions in the presence of potassium persulfate (KPS) as initiator and N,N'-methylene-bisacrylamide (MBA) as crosslinking agents at temperature 60 °C for 2 hours. The structure of the prepared SAP was confirmed using FTIR spectroscopy. The degree of swelling then was measured for all prepared samples in different types of water. The results showed that the degree of swelling of SAP samples as a function of AAc:AAm ratio were arranged as following: 1:2 > 1:3 > 1:1. In addition, as a function of water type, the different SAPs have greater absorbency of distilled water than deionized water, where tap water was recorded as a medium of lowest absorbency.